The Dimensions Of Functional And Aesthetic In The Works Of Calligrapher Roudan Bahia. (Journal of the College of Basic Education, 2024)
The research problem was represented by the question: (What are the dimensions of functional and aesthetic in the works of the calligrapher Raudan Baheya), and the aim of the research is (to reveal the functional and aesthetic dimensions in the works of the calligrapher Raudan Baheya). The theoretical framework included the following topics: The first topic / the concept of functional and aesthetic dimensions in art paintings The second topic / the functional and aesthetic foundations in artistic paintings, the third topic / the linear and decorative works in the paintings of the calligrapher Raudan Baheya, the research came out of the theoretical framework with indicators that were adopted in the design of a research tool for the purpose of analyzing samples according to the descriptive analytical approach in order to reach the achievement of the research results. The samples intentionally amounted to (four) samples, and results were reached, the most important of which were: the change in the design structures in the paintings, so they appeared in a form (architecture, or an icon in an unpainted engineering body, a decorative heart, a decorative vessel) and various bodies were employed in the structure of the design of the painting Among the occupations attached to plant motifs of units and shapes are decorative clouds, trees and birds, as well as the variation in the characteristics of systems such as the two-division system, the radial system and the asymmetric system, as these results highlighted The artistic productions of the calligrapher Roudan Bahiya are mature and perfect, as he possesses a unique creative sense